2018
DOI: 10.1111/apt.14808
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic response to CT‐P13 and infliximab originator in inflammatory bowel disease patients shows similar epitope recognition

Abstract: These results strongly support a similar antigenic profile for infliximab originator and CT-P13, and point toward a safe switching between the two drugs in anti-drug antibody negative patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…22 Other studies have also shown similar cross-immunogenicity results between INF, CT-P13, and SB2, 12,13,16,23 and similar functional inhibition of TNF-α binding. 12,16 The NOR-SWITCH study and its open-label extension showed that switching from INF to CT-P13 was not inferior to continued treatment with INF, and immunogenicity was not different between the two treatments. 24,25 Although the NOR-SWITCH study enrolled a large number of patients with varying diagnoses, the number of patients with IBD was relatively small in the main trial (Crohn disease, n = 155; ulcerative colitis, n = 93), which limits the ability to generalize to a larger population.…”
Section: Discussionmentioning
confidence: 61%
“…22 Other studies have also shown similar cross-immunogenicity results between INF, CT-P13, and SB2, 12,13,16,23 and similar functional inhibition of TNF-α binding. 12,16 The NOR-SWITCH study and its open-label extension showed that switching from INF to CT-P13 was not inferior to continued treatment with INF, and immunogenicity was not different between the two treatments. 24,25 Although the NOR-SWITCH study enrolled a large number of patients with varying diagnoses, the number of patients with IBD was relatively small in the main trial (Crohn disease, n = 155; ulcerative colitis, n = 93), which limits the ability to generalize to a larger population.…”
Section: Discussionmentioning
confidence: 61%
“…However, this increase was also associated with an increase in the reports of AE induced by IFX biosimilars [33]. This seems to contrast with a recent study by Gonçalves et al , who found a similar antigenic profile for IFX originator and IFX biosimilar CT-P13 [34]. Finally, the recent PROSIT Italian cohort study found a 19% rate of AE [23].…”
Section: Discussionmentioning
confidence: 93%
“…Thus, the clinical immunogenicity of biosimilars can be assessed relatively reliably (38). For example, results from a study comparing specific antigenic epitopes between CT-P13 and infliximab reference product have recently been reported, and suggest the two drugs have similar epitope binding profiles and equivalent immunogenicity (39).…”
Section: Demonstrating Anti-tnf Biosimilaritymentioning
confidence: 99%